2014
DOI: 10.1126/science.1258122
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast generation of pseudo-magnetic field for valley excitons in WSe 2 monolayers

Abstract: The valley pseudospin is a degree of freedom that emerges in atomically thin two-dimensional transition metal dichalcogenides (MX2). The capability to manipulate it, in analogy to the control of spin in spintronics, can open up exciting opportunities. Here, we demonstrate that an ultrafast and ultrahigh valley pseudo-magnetic field can be generated by using circularly polarized femtosecond pulses to selectively control the valley degree of freedom in monolayer MX2. Using ultrafast pump-probe spectroscopy, we o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
275
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(303 citation statements)
references
References 34 publications
14
275
2
2
Order By: Relevance
“…Fig 1d shows a pair of ∆α spectra measured using broadband probe pulses with helicities σ − (black) and σ + (red) at ∆t = 0.3 ps. This time delay was chosen to avoid contaminating effects of coherent light-matter interaction 7,8 . In contrast to what is expected, we observed strong bleaching peaks not only at A but also at B exciton transitions, and strikingly, these two peaks were present in both spectra measured using different helicities 22 .…”
Section: A Intervalley Biexcitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig 1d shows a pair of ∆α spectra measured using broadband probe pulses with helicities σ − (black) and σ + (red) at ∆t = 0.3 ps. This time delay was chosen to avoid contaminating effects of coherent light-matter interaction 7,8 . In contrast to what is expected, we observed strong bleaching peaks not only at A but also at B exciton transitions, and strikingly, these two peaks were present in both spectra measured using different helicities 22 .…”
Section: A Intervalley Biexcitonsmentioning
confidence: 99%
“…These include valley-selective photoexcitation [2][3][4] , valley Hall effect 5 , valley-tunable magnetic moment 6 , and valley-selective optical Stark effect 7,8 . Unlike traditional semiconductors, the Coulomb interaction in monolayer TMDs is unusually strong because screening is greatly suppressed and spatial overlap of the interaction is much larger.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 3.2b shows a pair of Aa spectra measured using broadband probe pulses with helicities a-(black) and a' (red) at At = 0.3 ps. This time delay was chosen to avoid contaminating effects of coherent light-matter interaction [29,30]. In contrast to what is expected, we observed strong bleaching peaks not only at A but also at B exciton transitions, and strikingly, these two peaks were present in both spectra measured using different helicities [37].…”
Section: Resultsmentioning
confidence: 80%
“…Unlike in the red-detuned experiments [29,30], the incoherent signals in our bluedetuned experiments are unavoidable and quite significant, because a large population of the absorption peak is Pauli blocked. Here we assume that the electron population has not rearranged themselves to occupy the shifted absorption peak, so that the bleaching profile is simply derived from the original absorption peak.…”
Section: Coherent and Incoherent Optical Signalsmentioning
confidence: 91%
“…The energy levels of these excitons can be tuned optically in a valley-selective manner by means of the optical Stark effect [5,6]. Prior research has demonstrated that monolayer TMDs driven by below-resonance (red-detuned) circularly polarized light can exhibit an upshifted exciton level, either at the K or K valleys depending on the helicity, while keeping the opposite valley unchanged.…”
mentioning
confidence: 99%